RELATIONSHIP BETWEEN KNOWLEDGE ABOUT CLIMATE CHANGE ISSUES AND LOCUS OF CONTROL WITH STUDENTS’ CITIZENSHIP BEHAVIOR - Erian Fatria (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2017)
Needless to say that environmental deterioration is brought about by the people intervention toward a nature. It has been assumed that people personality and intelligent influence the ecosystem. That is why the objective of this study is to find out relationship between knowledge about issues (KAI) and Locus of Control (LOC) with citizenship behavior (CB). In order meet with this objective, a survey method has been applied by involving 110 students as sample. There are three instruments, measuring knowledge about climate change issues, LOC, and students’ citizenship behavior (CB) and those have been validated. Regression and correlational analysis used to verify it relationship. Research results reveal that there is positive and significant correlation between knowledge about issues and CB, LOC and CB, finally between knowledge about issues and LOC with CB. These findings are still consistent even though first order correlation can be used to predict student’s citizenship behavior in term of how student live with nature harmoniously based on knowledge about issues and LOC. It could be concluded that in improving citizenship behavior, knowledge about issues and LOC cannot be neglected.